Idiopathic Bilateral Suprachoroidal Haemorrhage: A Rare Case Presentation. (28th June 2017) - Saluja, Komal; Naik, Mayuresh; Vemparala, Rajshekhar; Mehta, Anuj
Abstract : 55-year-old male presented with sudden onset painful diminution of vision in both eyes. On local examination, his visual acuity was FC at 2 metres in right eye and FC at 1 m in left eye. The IOP in right eye was 46 mm Hg and 44 mm Hg in left eye. The patient was admitted and started on injection mannitol, oral syrup glycerol, and oral acetazolamide. Locally, timolol maleate and brimonidine were also started. The next day, his IOP was 17 mm Hg bilaterally but his visual acuity deteriorated to FC 1 m in right eye and hand movement in left eye with inaccurate projection of rays in both eyes. USG B-scan was performed which revealed bilateral choroidal detachment. The echotexture of fluid was suggestive of haemorrhage. As the IOP was controlled, systemic hyperosmotic/antiglaucoma agents were withdrawn in stepwise fashion over next two days. The patient was started on oral prednisolone. At 2 weeks, the visual acuity in both eyes was only perception of light, with inaccurate PR. IOP was 10 mm Hg in both eyes. USG B-scan revealed resorption of the hemorrhage, with partial resolution of the choroidal detachment. The final BCVA was 6/18 and 6/12 in right and left eye.